(untitled) (Al-Mansour Journal, 2023)
This work investigates the estimation of the spectrum, when a frequency hopping (FH-SS) signal had been intercepted and determines the frequency of FH signal at maximum position using finite data records which are of major interest in military and commerical applications. The work has been accomplished using Matlab version 6.5. The FFT algorithm (periodogram) has been used to estimate the frequency of the hops. In the simulation, the frequency spacing between hops is taken to be 1 kHz and two frequencies are tested (50 kHz and 120 kHz).